A New Monoterpene from the Fruits of Ziziphus jujuba Mill and Its Antioxidant Activity - Yang, Xinzhou; Wei, Jie; Xu, Shitao; Li, Xuesen; Li, Zhong; Hu, Qiu-Fen (Asian Journal of Chemistry, 2011)
A new monoterpene 4-acetyl-3-hydroxy-6-isopropyl-pyran-2-one (m.f. C10H12O4) was isolated from the fruits of Ziziphus jujuba Mill. The structure was elucidated on the basis of extensive NMR and MS means. The antioxidant activity of the new monoterpene was evaluated and it showed antioxidant activity with an IC50 value of 3.53 μg/mL.